Demographics, Clinical Characteristics, Management, and Outcomes of Acute Heart Failure Patients: Observations from the Oman Acute Heart Failure Registry - Panduranga, Prashanth (Oman Med J, 2016)
OBJECTIVES: We sought to describe the demographics, clinical characteristics, management and outcomes of patients in Oman with acute heart failure (AHF) as part of the Gulf aCute heArt failuRe rEgistry (CARE) project. METHODS: Data were analyzed from 988 consecutive patients admitted with AHF to 12 hospitals in Oman between 14 February and 14 November 2012. RESULTS: The mean age of our patients was 63±12 years. Over half (57%) were male and 95% were Omani citizens. Fifty-seven percent of patients presented with acute decompensated chronic heart failure (ADCHF) while 43% had new-onset AHF. The primary comorbid conditions were hypertension (72%), coronary artery disease (55%), and diabetes mellitus (53%). Ischemic heart disease (IHD), hypertensive heart disease, and idiopathic cardiomyopathy were the most common etiologies of AHF in Oman. The median left ventricular ejection fraction of the cohort was 36% (27–45%) with 56% of the patients having heart failure with reduced ejection fraction (< 40%). Atrial fibrillation was seen in 15% of patients. Acute coronary syndrome (ACS) and non-compliance with medications were the most common precipitating factors. At discharge, angiotensin converting enzyme inhibitors and beta-blockers were prescribed adequately, but aldosterone antagonists were under prescribed. Within 12-months follow-up, one in two patients were rehospitalized for AHF. In-hospital mortality was 7.1%, which doubled to 15.7% at three months and reached 26.4% at one-year post discharge. CONCLUSIONS: Oman CARE was the first prospective multicenter registry of AHF in Oman and showed that heart failure (HF) patients present at a younger age with recurrent ADCHF and HF with reduced ejection fraction. IHD was the most common etiology of HF with a low prevalence of AHF, but a high prevalence of acute coronary syndrome and non-compliance with medications precipitating HF. A quarter of patients died at one-year follow-up even though at discharge medical therapy was nearly optimal. Our study indicates an urgent need for prevention, early diagnosis, and treatment of AHF in Oman.